Paradoks Efisiensi: Persepsi Pengguna dan Hambatan Sistemik dalam Implementasi Rekam Medis Elektronik - Naurah Zharifah; Daniel Happy Putra; Laela Indawati; Bangga Agung Satrya (Maranatha University Press, 2026)
This study aims to analyze the implementation of electronic medical record systems in improving the efficiency of health services. The approach used is a qualitative method with data collection techniques through in-depth interviews and observations of several health service units. The results of the study indicate that this system has a positive impact on accelerating the process of recording and accessing patient medical data, as well as reducing the use of physical documents. However, several challenges were also identified, such as limited technical training for healthcare staff and unstable internet connectivity. The conclusion of this study is that the electronic medical record system has the potential to improve the efficiency of healthcare services, but it requires support from comprehensive training and adequate technological infrastructure.